2020
DOI: 10.1108/ijssp-07-2020-0269
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic and teacher retention: empirical evidence from expat teachers in Southeast Asia during COVID-19

Abstract: PurposeThis research aims to explore the influence of expat teachers' attitude about local policies, and their subjective norms of social engagement during COVID-19 over their intention to leave the current country, due to COVID-19.Design/methodology/approachThis study uses analysis of variance (ANOVA) and structural equation model (SEM) to examine the perception of crisis and the intention to leave among 307 expat teachers in Southeast Asia during COVID-19 and highlights the importance of policy responses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 82 publications
1
25
0
4
Order By: Relevance
“…A large body of research have shown that parent-teacher collaboration contributes to overall school effectiveness [39,47,82]. Parent and teacher collaboration is vital for the academic and personal growth of students [64].…”
Section: Strategies For Onsite Learning Post Sars-cov-2mentioning
confidence: 99%
“…A large body of research have shown that parent-teacher collaboration contributes to overall school effectiveness [39,47,82]. Parent and teacher collaboration is vital for the academic and personal growth of students [64].…”
Section: Strategies For Onsite Learning Post Sars-cov-2mentioning
confidence: 99%
“…Khảo sát của chúng tôi với 373 giáo viên các cấp tại Hà Nội (Vu et al, 2020) vào tuần đầu tháng 4 ghi nhận 37,8% giáo viên cảm thấy mệt mỏi vì các xáo trộn do COVID-19, và 53,6% giáo viên có lo lắng về sự khó khăn kinh tế trong thời gian sắp tới. Trong một khảo sát khác với 307 giáo viên nước ngoài đang giảng dạy tại các nước Đông Nam Á , chúng tôi ghi nhận 45,6% cho rằng họ bị kì thị bởi người bản xứ vì những lo ngại liên quan đến COVID-19 (Hoang, 2020). Khi chính bản thân giáo viên cũng đang bị bủa vây bởi các căng thẳng, liệu các hoạt động và kết quả giáo dục sẽ tươi đẹp và không bị nhuốm màu căng thẳng?…”
Section: Kháng Thể Nào Cho Những Khát Khao?unclassified
“…It increases workload and pressure to improve learning quality (van der Spoel et al, 2020). For expatriate teachers in Southeast Asia, social restriction policies during the pandemic have disrupted financial conditions that can cause them to leave the country (Hoang, 2020). In America, the teaching process at this uncertain time experiences makes the high disparity between "real practice" and "ideal practice" (Quezada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%